(untitled) (Andamios, Revista de Investigación Social, 2006)
The purpose of this essay is to provide information about the strategies that have been developed through federal and institutional education policies that have been designed in order to lead academic work in our country toward a more professional level, highlighting the role held by Ph.D. programs as a central strategy since the eighties. This essay postulates the existence of determining phenomena such as the creation of an academic market and the identification of the need to professionalize academic work to attempt to explain a complex matter: the emergence and creation of an academic linked to a modern institution, subordinate to the permanent transformation caused by dynamic changes in contemporary society.